Safety and efficacy of rasagiline as an add-on therapy to riluzole in patients with amyotrophic lateral sclerosis: a randomised, double-blind, parallel-group, placebo-controlled, phase 2 trial. Issue 8 (August 2018) - Ludolph, Albert C; Schuster, Joachim; Dorst, Johannes; Dupuis, Luc; Dreyhaupt, Jens; Weishaupt, Jochen H; Kassubek, Jan; Weiland, Ulrike; Petri, Susanne; Meyer, Thomas; Grosskreutz, Julian; Schrank, Berthold; et al.
Summary: Background: Rasagiline, a monoamine oxidase B inhibitor with neuroprotective potential in Parkinson's disease, has shown a disease-modifying effect in the SOD1-Gly93Ala low-expressing mouse model of amyotrophic lateral sclerosis, both alone and in combination with riluzole. We sought to test whether or not rasagiline 1 mg/day can prolong survival in patients with amyotrophic lateral sclerosis also receiving riluzole. Methods: Patients with possible, probable, or definite amyotrophic lateral sclerosis were enrolled to our randomised, placebo-controlled, parallel-group, double-blind, phase 2 trial from 15 German network for motor neuron diseases (MND-NET) centres (university hospitals or clinics). Eligible patients were aged at least 18 years, had onset of progressive weakness within the 36 months before the study, had disease duration of more than 6 months and less than 3 years, and had a best-sitting slow vital capacity of at least 50%. After a 4-week screening period, eligible patients were randomly assigned (1:1) to receive either rasagiline (1 mg/day) or placebo in addition to riluzole (100 mg/day), after stratification for site of onset (bulbar or spinal) and study centre. Patients and all personnel assessing outcome parameters were masked to treatment allocation. Patients were followed up 2, 6, 12, and 18 months after randomisation. The primary endpoint was survival time, defined as the time to death or time to study cutoff date (ie, the last patient's last visit plus 14 days). Analyses of primary outcome and safety measures were done in all patients who received at least one dose of trial treatment (intention-to-treat population). The trial is registered with ClinicalTrials.gov, number NCT01879241 . Findings: Between July 2, 2013, and Nov 11, 2014, 273 patients were screened for eligibility, and 252 patients were randomly assigned to receive rasagiline (n=127) or placebo (n=125). 126 patients taking rasagiline and 125 taking placebo were included in the intention-to-treat analysis. For the primary outcome, the survival probability at the end of the study was 0·43 (95% CI 0·25–0·59) in the rasagiline group (n=126) and 0·53 (0·43–0·62) in the placebo group (n=125). The estimated effect size (hazard ratio) was 0·91 (one-sided 97·5% CI –infinity to 1·34; p=0·31). Rasagiline was well tolerated, and most adverse events were due to amyotrophic lateral sclerosis disease progression rather than treatment; the most frequent of these were dysphagia (32 [25%] taking rasagiline vs 24 [19%] taking placebo) and respiratory failure (25 [20%] vs 31 [25%]). Frequency of adverse events were comparable between both groups. Interpretation: Rasagiline was safe in patients with amyotrophic lateral sclerosis. There was no difference between groups in the primary outcome of survival, although post-hoc analysis suggested that rasagiline might modify disease progression in patients with an initial slope of Amyotrophic Lateral Sclerosis Functional Rating Scale Revised greater than 0·5 points per month at baseline. This should be confirmed in another clinical trial. Funding: Teva Pharmaceutical Industries.